Labor certification and employability of the Impulsa Peru program beneficiaries, 2011-2016 - Silva Suárez, Christian Omar (2020)
The study focused on the results obtained through the Labor Skills Certification service provided by the Impulsa Peru Program of the Ministry of Labor and Employment Promotion (MTPE) during the years 2011 - 2016, according to the regulations established by the General Directorate of Vocational Training and Labor Training (DGFPCL), as well as the guidelines of Budget Program 0116 “Improvement of Employability and Labor Insertion - PROEMPLEO”. These results were measured based on two key indicators such as the level of work experience and the level of salary, which are linked to the employability of a person. For this, four samples were taken whose size per sample was 1,804 beneficiaries with certified labor competencies and compared with 1,804 non-competent beneficiaries. It could be concluded that the permanence in the labor market had significance in the analysis of variance and in two of the four samples, showing differences of 1 to 3 months. On the other hand, the salary showed significance both in the analysis of variance and for the four samples compared, with differences between S / 30 to S / 70 soles. JEL: J01, E24, C2